Penilaian Kinerja Dan Metode Penilaian Kinerja - Putri, Nadhiyatul Aulia; Muhtady, Nazhir Hafni; Wahjono, Sentot Imam (CV ODIS, 2025)
This research aims to discuss performance appraisal and performance appraisal methods. The method used is library research, collecting data by searching for sources and constructing them from various sources such as books, journals and existing research. The result is that performance appraisal is the process of evaluating employees in completing tasks assigned by the organization. Performance appraisal methods are a way to assist management in carrying out the process of assessing employee performanc